Pengujian Manajemen Risiko Sebagai Variabel Moderasi Terhadap Hubungan Manajemen Laba dan Nilai Perusahaan - Eka Noor Asmara; D Djasamanuddin; S Supardi; Sidiq Ashari (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2023)
This study aims to examine the relationship between earnings management practices and firm value with enterprise risk management as a moderating variable. The sample in this research is 50 manufacturing companies listed on the Indonesia Stock Exchange during 2017-2021. The data collection technique was purposive sampling and derived from secondary data, both from the IDX and from the website of each company. The research hypothesis was tested using regression analysis. The results of the study show that earnings management has a significant negative effect on firm value. Risk management, which is expected to weaken the relationship between earnings management and firm value, is not supported in this study. Although risk management has not been significantly proven, this research contributes to stakeholders to encourage managers to maximize and optimize company risk management practices as an effort to prevent earnings management practices.